2021
DOI: 10.1093/jat/bkab066
|View full text |Cite
|
Sign up to set email alerts
|

Acute Intoxications Involving Valerylfentanyl Identified at the New York City Office of Chief Medical Examiner

Abstract: The detection of novel fentanyl analogs in both seized drugs and toxicological specimens has presented a significant challenge to laboratories with respect to identification, sourcing reference drug standards, time required for method development and ensuring sufficient method sensitivity. The New York City Office of Chief Medical Examiner (NYC OCME) has included testing for valerylfentanyl as part of a panel of synthetic opioids since May 2017 but did not identify the first valerylfentanyl positive case until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Extraction procedures utilized for LC–MS/MS quantitative methods are more expansive due to the applicability to multiple matrix types. While LLE [21,38,39,40,41,42,43,44,45] and SPE [23,37,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70] remain the most common techniques, PP [17,71,72,73,74,75,76,77,78,79,80,81,82], simple dilution [11,14,37,83] solvent extraction [82,84,85], SLE [86,87] and QuECHeERs [16,71,88] have been described as suitable extraction techniques among their evaluated scenarios. In some studies, sample pretreatment techniques such as PP and physical preparations (grinding [89,90], pulverization [62], and digestion [37]) were employed before extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Extraction procedures utilized for LC–MS/MS quantitative methods are more expansive due to the applicability to multiple matrix types. While LLE [21,38,39,40,41,42,43,44,45] and SPE [23,37,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70] remain the most common techniques, PP [17,71,72,73,74,75,76,77,78,79,80,81,82], simple dilution [11,14,37,83] solvent extraction [82,84,85], SLE [86,87] and QuECHeERs [16,71,88] have been described as suitable extraction techniques among their evaluated scenarios. In some studies, sample pretreatment techniques such as PP and physical preparations (grinding [89,90], pulverization [62], and digestion [37]) were employed before extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the first 6 months of 2022, acetylfentanyl and fluorofentanyl were identified in 124 and 554 postmortem cases, respectively. In the vast majority of cases where fentanyl analogs are present, fentanyl is also detected and there are few cases where a fentanyl analog is present alone, either as the only drug or only opioid present [7,8].…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…By March 2021, the method had been further expanded to 44 synthetic opioids plus xylazine. The detailed method parameters, including the list of synthetic opioids, were previously published [7,8] with limits of detection (LOD) of 0.05 and 0.10 ng/mL for fentanyl and fentanyl analogs.…”
Section: Me Thodsmentioning
confidence: 99%
“…In the 1980s, researchers recognized the need for reference materials to confirm the identity of fentanyl analogs and to evaluate their potency, therefore synthesizing many of which are re‐emerging today 4,5 . Valerylfentanyl was included as one of these compounds, and since then, it has been detected in wastewater effluents, postmortem samples, or seized drugs in North America, Australia, Europe, and Asia 6–11 . Figure 1 shows the structure of valerylfentanyl, a homolog of fentanyl, differing by 28 Da.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Valerylfentanyl was included as one of these compounds, and since then, it has been detected in wastewater effluents, postmortem samples, or seized drugs in North America, Australia, Europe, and Asia. [6][7][8][9][10][11] Figure 1 shows the structure of valerylfentanyl, a homolog of fentanyl, differing by 28 Da. A study of valerylfentanyl in monkeys showed that it was equipotent to morphine.…”
mentioning
confidence: 99%